Phenotypic and genotypic characterization of Streptococcus spp. isolated from tilapia (Oreochromis spp.) cultured in river-based cage and earthen ponds in Northern Thailand - Guoyi Niu (2020)
© 2020 John Wiley & Sons Ltd Streptococcus spp. are major pathogenic bacteria associated with massive mortality in tilapia. This study investigated the phenotypic and genotypic characterization of Streptococcus agalactiae (GBS) and Streptococcus iniae (S. iniae) isolated from tilapia in river-based floating cage and earthen pond farms in northern Thailand. Isolates were identified by biochemical and molecular analyses. Capsular typing, enterobacterial repetitive intergenic consensus polymerase chain reaction and multilocus sequence typing were performed to investigate the genetic relatedness. Six and one isolates were confirmed as GBS and S. iniae, respectively. All Streptococcus spp. isolates were obtained from 4 river-based cage farms (4/33), while samples collected from earthen pond farms (N = 28) were negative for streptococcosis. All GBS with serotype Ⅲ and sequence type (ST) 283 was observed. The β-haemolytic GBS isolates were resistant to five antimicrobials, while the S. iniae was susceptible to all antimicrobials. This study indicates both GBS and S. iniae are the major bacterial pathogens responsible for streptococcosis infection in farmed tilapia of northern Thailand with GBS as dominant species. This survey highlights that the river-based cage farms seriously impact on the healthy development of the tilapia industry.